Perbaikan Sistem Distribusi dan Inventori pada PT. Blue Sky Biotech - Mudita, Albertus Arya; Octavia, Tanti; Widyadana, Gede Agus (Jurnal Titra, 2015)
This paper discusses about inventory and distribution systems in PT. Blue Sky Biotech branch especially in Surabaya. Surabaya branch often has too much Prosatu product in the end of the month and the distribution systems also still infefficent. The analysis of distribution and inventory systems will affect to the total cost and and the warehouse inventory itself. The distribution system will be analyzed from distriburion route at Jakarta, choosing distribution partner, and the distribution method itself. There is an elimination route of taman tekno-gunung sindur-taman tekno route to minimize transportation cost. For the distribution partner PT. Blue Sky Biotech has three alternatives, to use existing partner (using bus) or to change it with train or truck. Continuous review policy with reorder point method is proposed to control the inventory. The best alternative is the company deliver the products using truck, as distribution partner and continuous review policy to control the inventory. The combination can reduce the company expense around 64%.